The Effect of Lifestyle on the Incidence of Hypertension in the Working - Aoladul Muqarrobin; Erwin Wiksuarini; Baiq Fitrihan Rukmana; Aghil Adha (Citra Delima Scientific journal of Citra Internasional Institute, 2026)
Hypertension is one of the non-communicable diseases that has become a major global public health problem and a leading cause of cardiovascular disease. Lifestyle factors, including diet, physical activity, and smoking habits, play an important role in the onset of hypertension. This study aimed to determine the relationship between lifestyle and the incidence of hypertension in the working area of Janapria Public Health Center, Central Lombok Regency. This research employed a quantitative approach with a cross-sectional design. The sample consisted of 62 respondents with hypertension selected using purposive sampling. Research instruments included a questionnaire to assess lifestyle and blood pressure measurement using a sphygmomanometer. The univariant results showed that most respondents had a sufficient lifestyle, as many as 34 respondents. Then, the blood pressure of most respondents was grade 1 hypertension, as many as 32 respondents. Bivariate analysis using the Chi-Square test showed a significant relationship between lifestyle and the incidence of hypertension (p=0.000).  The conclusion of this study is that lifestyle is related to hypertension, where an unhealthy lifestyle increases the risk of hypertension. Health education, promotion of healthy diets, regular physical activity, and stress management efforts are needed to reduce the incidence of hypertension.